A qualitative study comparing experiences of the surgical safety checklist in hospitals in high-income and low-income countries. Issue 8 (15th August 2013) - Aveling, Emma-Louise; McCulloch, Peter; Dixon-Woods, Mary
Abstract : Objective: Bold claims have been made for the ability of the WHO surgical checklist to reduce surgical morbidity and mortality and improve patient safety regardless of the setting. Little is known about how far the challenges faced by low-income countries are the same as those in high-income countries or different. We aimed to identify and compare the influences on checklist implementation and compliance in the UK and Africa. Design: Ethnographic study involving observations, interviews and collection of documents. Thematic analysis of the data. Setting: Operating theatres in one African university hospital and two UK university hospitals. Participants: 112 h of observations were undertaken. Interviews with 39 theatre and administrative staff were conducted. Results: Many staff saw value in the checklist in the UK and African hospitals. Some resentment was present in all settings, linked to conflicts between the philosophy behind the checklist and the realities of local cultural, social and economic contexts. Compliance—involving use, completeness and fidelity—was considerably higher, though not perfect, in the UK settings. In these hospitals, compliance was supported by established structures and systems, and was not significantly undermined by major resource constraints; the same was not true of the low-income context. Hierarchical relationships were a major barrier to implementation in all settings, but were more marked in the low-income setting. Introducing a checklist in a professional environment characterised by a lack of accountability and transparency could make the staff feel jeopardised legally, professionally, and personally, and it encouraged them to make misleading records of what had actually been done. Conclusions: Surgical checklist implementation is likely to be optimised, regardless of the setting, when used as a tool in multifaceted cultural and organisational programmes to strengthen patient safety. It cannot be assumed that the introduction of a checklist will automatically lead to improved communication and clinical processes.